Enantioselective Transfer Hydrogenation of Oxocarbenium Ions Enables Asymmetric Access to α-Substituted 1,3-Dihydroisobenzofurans - Zhou, Likai; Jia, Kuiyong; Liu, Xigong; Liu, Lei (Synthesis, 2021)
Reported here is an efficient enantioselective transfer hydrogenation of cyclic oxocarbenium ions generated in situ through collapse of the corresponding acetal substrates. The asymmetric approach provides straightforward access to a variety of chiral α-aryl substituted 1,3-dihydroisobenzofurans in high yields with excellent enantioselectivities. α-Alkynyl substituted 1,3-dihydroisobenzofurans were also proved to be suitable substrates. In addition, when the reaction was performed at gram scale, the desired product was obtained in good yields with excellent enantioselectivity.
Keywords: enantioselectivity; transfer hydrogenation; oxocarbenium ions; α-substituted 1,3-dihydroisobenzofurans; asymmetric catalysis